2020
DOI: 10.1038/s41598-020-77207-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term myofibroblast persistence in the capsular bag contributes to the late spontaneous in-the-bag intraocular lens dislocation

Abstract: Late spontaneous in-the-bag intraocular lens (IOL) dislocation is a complication presenting 6 months or later after cataract surgery. We aimed to characterize the cells in the lens capsules (LCs) of 18 patients with spontaneous late in-the-bag IOL dislocation. Patients' average age was 82.6 ± 1.5 years (range 72–98), and most of them had pseudoexfoliation syndrome (PEX). Cells from the LCs were positive for myofibroblast (αSMA), proliferation (Ki-67, PCNA), early lens development/lens progenitor (SOX2, PAX6), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 99 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, the involvement of myofibroblasts in CBD has been reported in pseudoexfoliation syndrome. 16 In this study, we observed low-density fibrosis in the AD group and a qualitative comparison of myofibroblasts in the capsules of the AD and non-AD groups may be useful.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, the involvement of myofibroblasts in CBD has been reported in pseudoexfoliation syndrome. 16 In this study, we observed low-density fibrosis in the AD group and a qualitative comparison of myofibroblasts in the capsules of the AD and non-AD groups may be useful.…”
Section: Discussionmentioning
confidence: 70%
“…Proliferating cell nuclear antigen (PCNA) and Ki-67 are two indicators that can well delineate the proliferation of cells. 28 F I G U R E 7 Expression of Cyclin A, Cyclin D1, PCNA, and Ki-67 in primary mouse renal mesangial cells (MRMCs, A) and SV40 MES-13 cells (B). * P < 0.05 versus Blank group and Control activation particles group; # P < 0.05 versus SOCS-3 activation particles group; & P < 0.05 versus SOCS-3 siRNA group.…”
Section: Discussionmentioning
confidence: 99%
“…After 3 months, the contraction of the capsular bag slows down and tends to stabilize ( 4 , 17 ). However, with recent in-depth studies, we have found that the course of ACCS can develop in the weeks to years following surgery and in high-risk patients such as those with pseudoexfoliation (PEX), high myopia, and RP, the incidence of ACCS may increase to 10% to 30% or more ( 18 , 19 ). Furthermore, a comprehensive population study with a 30 years follow-up indicates that late in-the-bag IOL dislocation can occur after cataract surgery, ranging from 6 months to 25 years or even longer, and it is associated with zonular dehiscence and capsular bag contraction ( 20 , 21 ).…”
Section: Incidence and Course Of Accsmentioning
confidence: 96%
“…This can further contribute to the occurrence of ACCS. Additionally, PEX is the most common underlying condition for spontaneous in-the-bag IOL dislocation ( 19 ). It is currently believed that implanting a CTR or postoperative use of nonsteroidal anti-inflammatory drugs (NSAIDs) can be effective in reducing postoperative ACCS in patients with PEX ( 62 , 67 , 68 ).…”
Section: Influencing Factors For Accsmentioning
confidence: 99%